Swelling pressure of compacted bentonite acting on constraining material with deformability. Issue 12 (22nd September 2021) - Watanabe, Yasutaka; Tanaka, Yukihisa
Abstract : In order to better understand the physical interactions between compacted bentonite and the host rock, the swelling pressure acting on a constraining material with slight deformability and the volume change of the compacted bentonite caused by unloading without consolidation history were investigated. A swelling test apparatus equipped with controls for applying a small strain and loading pressure was developed to mechanically simulate the elastic strain of a soft and a hard rock and large deformation of the constraining materials. After the equilibrium swelling pressure had been measured, the vertical pressure was unloaded. It was found that the slight deformation of the compacted bentonite decreased the swelling pressure. Furthermore, upon unloading, for the Na-bentonite with no consolidation history, after the equilibrium swelling pressure had been measured by a sufficiently confined condition, the slope angle of the unloading curve approximately equalled that of the normal consolidation line, although a slight non-linearity of the curve was observed in highly compacted bentonite. Based on the Mohr–Coulomb yield criterion, this indicated a mechanism whereby the shear strain in the saturation and one-dimensional swelling deformation processes effects an isotropy of swelling pressure and a non-linearity of the unloading curve.